Analisis Spasial Tingkat Kerawanan Kebakaran Hutan dan Lahan di Kabupaten Indragiri Hulu - Afrizal, Deden; Putra, Ridwan Manda; Syafii, Muhammad (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Forest and land fires in Indragiri Hulu district have increased significantly in the last five years. Overall in the last five years the total area of land and forest that has been burned due to forest and land fires that were burned intentionally or not exceeds 1600 hectares. As one of the districts that has a high plantation area and production of garden crops, making forest and land fires is one of the challenges faced. Therefore, it is necessary to assess the level of risk of forest and land fire vulnerability. As one of the techniques that can analyze the level of risk of such vulnerability spatially, the use of geographic information systems (GIS) is very supportive for the analysis of this level of vulnerability spatially. As a determinant of the level of vulnerability, several parameters are used, namely soil type, land cover, rainfall, population and infrastructure. The results of this level of risk and vulnerability show that several sub-districts in Indragiri Hulu district have a very high level of forest and land fire vulnerability. These districts include Rengat, West Rengat, Kuala Cenaku, Batang Gangsal, Seberida, Batang Cenaku, Rakit Kulim and Peranap.